Communication from the governor relative to Abraham Lincoln's proclamation of emancipation : January 20, 1863 (Document (Virginia. General Assembly. Senate), 1863)
January 20, 1863 Communication of Governor Letcher to the General Assembly, responding to President Lincoln's Emancipation Proclamation. Of note, he was against it and so advised the legislature.